Woman hygiene practice in Malaysia: a quantitative study - Nor Dalila Marican; N. Azmawati; H. Rozita; Muhamad Saufi Che Rusuli; M.Y. Nurul Hafizah; N. Nurhaiza (2017)
Diarrhea disease is one of the leading causes of death for children below 5 year of age. It is preventable and treatable disease and also greatly affects society and economy. The World Health Organization (WHO) and United Children’s Fund (UNICEF) has tried to encourage communities and families to promote desirable hygienic behavior. A cross sectional study was carried out in Mei-December 2013 in Kuala Terengganu district, Malaysia to determine the prevalence of diarrhea and practice of hygiene among women who manage homes. A total number of 216 women have been selected by using convenience sampling selection method. Data was collected using Hygiene-Q questionnaire. Data was analyzed by using SPSS version 19.0. The response rate was (100%). Age of respondents was between 20-55 year old with the mean age of 39.8±8.2 year. Majority of respondents received secondary education (54.2%) and most of them are working (56%). Result indicated that 23.1% respondents and 15.3% household having diarrhea. Generally, respondents practice good hygiene behavior (84.7%); hand washing (85.6%); food preparation (87%); environmental cleanliness (51.4%) and water usage (86.1%). Bivariate chi-square analysis indicated that there were seven factors significantly associated with diarrhea including age, education level, occupation, household’s income, hand washing, food preparation, environmental cleanliness and water usage. Multiple logistic regressions showed that the water usage is a significant predictor to the occurrence of diarrhea. Therefore, majority (84.7%) of the women who manage home have good hygiene behavior practice. Factors of age, ethnic and marital status did not influence the practice of hygiene behavior. Similarly, the demographic features of ethnic, marital status and occupational did not influence occuring of diarrhea. However, respondent who practice good hygiene behavior have lower risk having diarrhea.